Harnessing fold-to-wrinkle transition and hierarchical wrinkling on soft material surfaces by regulating substrate stiffness and sputtering flux. Issue 32 (31st July 2018) - Yu, Senjiang; Sun, Yadong; Li, Shichen; Ni, Yong
Abstract : We developed a facile technique to harness fold-to-wrinkle transition and hierarchical wrinkling on soft material surfaces by regulating substrate stiffness and sputtering flux. Abstract : Strain-induced complex surface patterns such as wrinkles, folds and hierarchical structures are quite useful in a wide range of practical applications. Although various surface patterns have been extensively investigated, precisely controlling the coexistence and transition of multimodal structures is still a challenge. In this work, we report on a facile technique to harness fold-to-wrinkle transition and hierarchical wrinkling on soft material surfaces by regulating substrate stiffness and sputtering flux. It is found that as the substrate stiffness or sputtering flux increases, the surface patterns successively evolve from networked folds to isolated folds (coexistence of folds and wrinkles) and finally to labyrinth-like wrinkles. For larger sputtering flux, two distinct wrinkling patterns ( i.e., G1 wrinkling due to surface instability during sputtering and G2 wrinkling due to thermal compression after deposition) can coexist on the sample surfaces, resulting in the spontaneous formation of hierarchical wrinkles. The report in this work could promote better understanding of the sputtering effect on the spontaneous pattern formation for soft materials and controllable fabrication of multiple complex patterns by simply regulating substrate stiffness and sputtering flux.